Determination of triterpenoid saponin and polysaccharide content from in vitro cultures of Astragalus mongholicus Bunge - Tsolmon Munkhbayar; Batzaya Gachmaa; Azzaya Jukov; Oyunbileg Yungeree (Proceedings of the Mongolian Academy of Sciences)
In this study, the efficient micropropagation protocol of Astragalus mongholicus Bunge was established and also triterpenoid saponin and polysaccharide content in ethanol, methanol and aqueous extracts of different samples were determined by using spectrophotometric methods to investigate whether the content of biologically active compounds depends on the stage of development of the plant during in vitro culture. The content of total saponins and polysaccharides in different cultures of A. mongholicus grown in vitro was higher (990 and 505 μg/ml) in ethanol extracted 14-day-old young shoot samples than in 28-day-old propagated shoot samples and rooted shoots.